2019
DOI: 10.1080/1828051x.2018.1549963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lycopene and tomato paste on oxidative stability and fatty acid composition of fresh belly meat in finishing pigs

Abstract: The present study was undertaken to investigate the effects of dietary lycopene and tomato paste on plasma lipids, malondialdehyde (MDA) concentrations and fatty acid composition of fresh belly meats from finishing pigs. In addition, lycopene concentrations in fresh belly meat were measured. A total of 60, 18-week-old crossbred pigs (Landrace  Yorkshire  Duroc) were fed four dietary treatments for four weeks. The diets included a base diet of maize and soybean meal (control treatment) and the base diet mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The colour evaluation of meat samples showed that the concentration of TP had significant (P < 0.05) effects on the colour of raw chicken sausage samples (Table 2). Similar results have been observed in previous studies by adding tomato products to the color changes of grilled turkey breast (Skiepko et al, 2016), minced chicken (Alves et al, 2012), beef (Østerlie & Lerfall, 2005) and pork (An et al, 2019) samples.…”
Section: Color Measurementssupporting
confidence: 91%
“…The colour evaluation of meat samples showed that the concentration of TP had significant (P < 0.05) effects on the colour of raw chicken sausage samples (Table 2). Similar results have been observed in previous studies by adding tomato products to the color changes of grilled turkey breast (Skiepko et al, 2016), minced chicken (Alves et al, 2012), beef (Østerlie & Lerfall, 2005) and pork (An et al, 2019) samples.…”
Section: Color Measurementssupporting
confidence: 91%
“…As in this study, that reaction shows a reduced concentration of malonaldehyde in the LL muscle. An et al [ 8 ] also observed that the inclusion of 20 mg of lycopene/kg of diet resulted in lower MDA concentrations in fresh pork belly meats of finishing pigs and observed significant values of lycopene in meat and no change in the fatty acid composition of fresh belly meat. In this way, it is suggested that enhanced oxidative stability of pork meat is due to the incorporation of lycopene, rather than lycopene-induced alteration of fatty acid composition or lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already shown improvements in pork quality of pigs fed diets with lycopene. Finishing pigs receiving 20 mg lycopene/kg of diet showed lower malondialdehyde (MDA) concentrations in fresh belly meat [ 8 ]. The inclusion of tomato processing by-products in pig diets during a seven weeks period improved the pork softness [ 9 ] and the inclusion of 5.0% of this byproduct in the diet increased the oxidative stability of pork, improving its nutritional quality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…158 It was found that the production performance of hybrid fattening pigs was not affected after adding lycopene (12.5, 25.0, 37.5 and 50.0 mg kg −1 ) to their diets for 4 weeks. 159 This may be due to differences in pig breeds, feeding management, and other factors, resulting in various research results. Although lycopene can improve the production performance of sows, further tests are needed to verify the positive effect of lycopene on pig production performance.…”
Section: Applicationmentioning
confidence: 99%